Improving Volleyball Bottom Passing Learning Results Through Playing Ball Throwing - Riyan Jaya Sumantri; Ridwan Afandi; Yuning Eka Rahma Wati; Mudayat Mudayat; Ahmad Syarif (Yayasan Insan Mulia Bima, 2023)
Volleyball is a team sport, so players must work together and support each other to form a cohesive team. The purpose of this study was to find the application of the ball throwing technique to improve volleyball underhand passing learning in Class IV SD N 1 Sikayu. This study used a classroom action research design which was carried out in two cycles, namely planning, implementing action, observing, and reflecting. Data on volleyball learning outcomes were collected through proficiency tests and observation sheets were used to collect data on student activities in participating in the volleyball learning process using the ball throwing method. The results showed a significant increase from Cycle I to Cycle II. The results of the evaluation in the first cycle were 50% with the